PCK component integration frequency raw data of elementary education teacher educators about biodiversity - Ottogalli, Maria Emilia (2025)
Biodiversity is a very important topic nowadays, but there is currently a lack of studies on the Pedagogical Content Knowledge (PCK) of this concept. We examined the integration of the PCK components of ten elementary education teacher educators in Argentina through a qualitative, interpretative, and exploratory study, using semi-structured interviews based on the Content Representation tool and the mapping approach. OTS and KSU were most integrated while KA was the least integrated. We discuss the implications of integration between PCK components for biodiversity teaching as a contribution to teacher training and future research.